(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This work takes a particular way to study social memories, situated in a particular group that constructs these memories, such as indigenous communities. Specifically, the collective memories of Mapuche communities is approached through sacred practices and ceremonies. The ritual of Camaruco, tayïl and dreams are analyzed in the mark of psychosocial constructions of identity, knowledge, and memories. Therefore, in this article we take the actions in which the community is linked to the ancestors and renew their belonging to the Mapuche people, intertwining the experiences of the present with the previously experienced, being the memory that articulates the inherited, shaping it in current experiences and establishing a relationship with the ancestors to guide the future of the community. This “memory into action” is created in the same action where it is shared through relations- hips that will sustain that social memory.